Basketball small-sided games : effects of varying formats and using successive bouts - Clemente, Filipe Manuel (Array, 2021)
This study compared athletes" rate of perceived exertion (RPE) and the number of their technical-tactical actions in small-sided basketball games (SSG) played within the same relative area with adjusted bout durations in (a) varied game formats; and (b) in two successive bouts of different formats. Ten young female basketball players (14.3±1.3 years) played two bouts of five small-sided game (SSG) formats (1x1, 2x2, 3x3, 4x4, and 5x5). The number of technical-tactical actions per player per minute decreased from the smaller to the larger SSG format, and players" RPE tended to be higher in larger compared to smaller formats. We concluded that the smaller basketball SSG formats increased players" participation. In addition, adjustments of the relative playing area and bout duration seemed to decrease players" effort. The use of two SSG bouts did impact the number of technical-tactical actions and RPE.